Klasifikasi Diabetes Menggunakan Algoritma Support Vector Machine Radial Basis Function - Muhammad Hilmy Haidar Aly (Jurnal Teknik Informatika dan Teknologi Informasi, 2024)
Diabetes mellitus (DM) is a chronic disease associated with high levels of sugar or glucose in the blood caused by pancreatic and insulin disorders. According to data from the Ministry of Health of the Republic of Indonesia, Diabetes is the third leading cause of death in Indonesia with a percentage of 6.7%. The high rate prompted this study to conduct early detection. One approach that has been widely used is the use of the Support Vector Machine algorithm in predictive modeling. The method was chosen because it was proven in previous studies to get quite high accuracy. Several preprocessing methods were performed to prepare the data for the classification process. The data used involved parameters such as pregnancy, glucose, blood pressure, skin thickness, insulin, weight, heredity, and age. Based on experimental results in ongoing system testing, the maximum performance result is 87% using SVM.